2015
DOI: 10.1007/s00216-015-9008-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of sphingosine 1-phosphate by validated LC-MS/MS method revealing strong correlation with apolipoprotein M in plasma but not in serum due to platelet activation during blood coagulation

Abstract: Sphingosine 1-phosphate (S1P) is a signalling sphingolipid affecting multiple cellular functions of vascular and immune systems. It circulates at submicromolar levels bound to HDL-associated apolipoprotein M (apoM) or to albumin. S1P in blood is mainly produced by platelets and erythrocytes, making blood sampling for S1P quantification delicate. Standardisation of sampling is thereby of great importance to obtain robust data. By optimising and characterising the extraction procedure and the LC-MS/MS analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
4
56
1
Order By: Relevance
“…In contrast to our data, one study detected increased serum S1P levels in patients with liver fibrosis [13]. However, due to the activation of platelets during the clotting process, serum is supposed to be an inadequate sample matrix to reflect S1P levels at the time of blood sampling [14]. Another study, including 15 patients with chronic hepatitis C infection, revealed a decrease of S1P levels with increasing progression of liver fibrosis [15], which supports our findings.…”
Section: Discussioncontrasting
confidence: 90%
“…In contrast to our data, one study detected increased serum S1P levels in patients with liver fibrosis [13]. However, due to the activation of platelets during the clotting process, serum is supposed to be an inadequate sample matrix to reflect S1P levels at the time of blood sampling [14]. Another study, including 15 patients with chronic hepatitis C infection, revealed a decrease of S1P levels with increasing progression of liver fibrosis [15], which supports our findings.…”
Section: Discussioncontrasting
confidence: 90%
“…Determining tissue expression of S1P under varying conditions will be a challenging target of further work and will be important to evaluate the role of this new pathway in the regulation of bone differentiation. Measurements of S1P in serum indicate that it circulates at concentrations of 500 to 1000 nM, albeit significantly protein bound and in some circumstances released by platelet activation. Carriers of S1P include albumin and apolipoprotein M; in serum, S1P is important in vascular homeostasis and immune cell response .…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of literature reports is complicated by the fact that quantification of plasma S1P is notoriously cumbersome and over time a vast number of different procedures have been employed for its measurement. The use of different analytical techniques by researchers might have contributes to the variations in reported ranges of S1P in plasma of normal individuals (200 to 840 nM) [4,5,8,21,22]. The quantification of S1P is challenging due to its zwitterion character, even more so the determination of relatively low levels in a complex matrix of other lipids.…”
Section: Introductionmentioning
confidence: 94%